ANALISIS PELUANG DAN TANTANGAN LEMBAGA KEUANGAN SYARIAH UNTUK MENINGKATKAN DAYA SAING MENGHADAPI MASYARAKAT EKONOMI ASEAN - Yayat Rahmat Hidayat (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2018)
Indonesia has a big potential in the development economic of sharia, it has a large number of Muslim population and abundant natural resources that can be used as an underlying transaction in sharia economy. But lots of obstacles has been faced by Indonesia while developing its sharia economy so that they have low competitiveness compared with conventional financial institutions and sharia financial institutions from other ASEAN countries, especially Malaysia. Obstacles that were mentioned are the lack of human resources sharia economy in both quantity and quality, the lack of knowledge and awareness in economic sharia, the lack of innovation and product differentiation, and lack of support from either government regulation or the issuance of capital. It is necessary to provide efforts and strategies to improve the sharia economic competitiveness in order to win the competition at the ASEAN Economic Community (AEC). Efforts and strategies may include the improvement of human resources in both quality and quantity, socialization and education in the community, service improvement and product differentiation, and the support from all of the stakeholders.